2000
DOI: 10.1046/j.1469-8137.2000.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus concentrations in the leaves of defoliated white clover affect abscisic acid formation and transpiration in drying soil

Abstract: Increased leaf phosphorus (P) concentration improved the water-use efficiency (WUE) and drought tolerance of regularly defoliated white clover plants by decreasing the rate of daily transpiration per unit leaf area in dry soil. Night transpiration was around 17% of the total daily transpiration. The improved control of transpiration in the high-P plants was associated with an increased individual leaf area and WUE that apparently resulted from net photosynthetic assimilation rate being reduced less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 43 publications
0
18
0
2
Order By: Relevance
“…Higher concentrations of P in plants improve WUE because they allow a minor suppression of photosynthesis per unit of water transpired (Singh et al, 2000;Jones et al, 2005) and improve the capacity of stomatal control (Waraich et al, 2011). Enzymes of N metabolism play an important role in the acclimation to drought (Xu and Zhou, 2006).…”
Section: Drought Shifts In Elemental Compositionmentioning
confidence: 99%
“…Higher concentrations of P in plants improve WUE because they allow a minor suppression of photosynthesis per unit of water transpired (Singh et al, 2000;Jones et al, 2005) and improve the capacity of stomatal control (Waraich et al, 2011). Enzymes of N metabolism play an important role in the acclimation to drought (Xu and Zhou, 2006).…”
Section: Drought Shifts In Elemental Compositionmentioning
confidence: 99%
“…Th is has a direct eff ect on the photosynthetic capacity and an indirect eff ect on water use effi ciency (WUE). In fact, several experiments have observed that low nutrient availability can diminish WUE (Sing et al, 2000;Ruiz-Lozano et al, 2001). If drought changes the N availability in soil, it will also aff ect the capacity of plants to capture N, thus aff ecting WUE, since WUE is positively correlated with leaf N concentration (Sing et al, 2000;Ruiz-Lozano et al, 2001;Fernández et al, 2006).…”
Section: Soil Enzyme Activity In a Mediterraneanmentioning
confidence: 99%
“…Partitioning more biomass to roots and maintaining higher root shoot ratio are advantageous to drought-adapted plants as drought and nutrient stress occur, because greater water absorptive component (fine root) can sustain more water and nutrient uptake for transpiration and respiratorion (Singh et al, 2000;Gleeson and Good, 2003;Qu et al, 2003).…”
Section: Interactive Effects Of Water N and P To Seedlings Functionmentioning
confidence: 99%